Application of the Treffinger Learning Model Assisted by Image Media to Improve Poetry Writing Skills in Class XI Students of SMAN 6 Karawang: Penerapan Model Pembelajaran Treffinger Berbantuan Media Gambar untuk Meningkatkan Keterampilan Menulis Puisi pada Siswa Kelas XI SMAN 6 Karawang - Mega Rachmawati Arum Permatasari; Sinta Rosalina; Hendra Setiawan (Santhet: (Jurnal Sejarah, Pendidikan Dan Humaniora), 2024)
Students experiencing difficulty in writing poetry is one of the backgrounds for this research. This research aims to determine the increase in the ability to write poetry in the learning process that applies the treffinger learning model assisted by image media versus those that do not apply the treffinger learning model assisted by image media. The research method used was a quasi experiment in the form of Nonequivalent Control Group Design. The population in this study were class XI students of SMAN 6 Karawang. Sampling was carried out using a purposive sampling technique by selecting two classes, namely XI-5 (control class) and XI-2 (experimental class), each with 36 student respondents from 324 class XI students. The results of this research show that the application of the treffinger learning model assisted by image media has been proven to be able to increase the ability to write poetry in the experimental class and the control class and there are significant differences. This conclusion can be seen from the results of the pretest and posttest scores which have significant differences in the experimental and control classes. The control class had an average pretest score of 53.64 and posttest 70.78. Meanwhile, the experimental class had an average pretest score of 64.53 after implementing the Treffinger learning model assisted by image media which increased with an average posttest score of 80.56.